Properties of ShB A-type potassium channels expressed in Shaker mutant Drosophila by germline transformation. - Zagotta, W.N.; Germeraad, S.E.; Garber, S.S.; Hoshi, T.; Aldrich, R.W. (Neuron, 1989)
We have used P element-mediated germline transformation to express ShB channels in Shaker mutant Drosophila and have examined their properties by patch-clamp of embryonic myotubes. The transformed ShB cDNA was placed under the transcriptional control of a heat shock promoter (hsp70). Northern blots revealed that transformed DNA is efficiently transcribed in response to heat shock. Cultured myotubes from the transformants produced large A-type potassium currents in response to heat shock. Although qualitatively similar to native Shaker A-currents in wild-type myotubes, transformant A-current inactivates more rapidly and recovers from inactivation more rapidly, similar to ShB channels expressed in Xenopus oocytes. Unlike the channels in oocytes, however, the transformant A-current is insensitive to 50 nM charybdotoxin.